The removal of anionic surfactants from water in coagulation process - Kaleta, Jadwiga (Environmental technology, 2013)
This paper presents the results of a laboratory study on the effectiveness of the coagulation process in removing surfactants from water. The application of traditional coagulants (aluminium sulfate and iron chlorides) has not brought satisfactory results, the reduction in anionic surfactant (AS) content reached 7.6% and 10%, respectively. Adding cationic polyelectrolyte (Zetag-50) increased the removal efficiency to 24%. Coagulation using a polyelectrolyte alone proved to be more efficient, the reduction in surfactant content fluctuated at a level of about 50%. Complete surfactant removal was obtained when powdered activated carbon was added 5 minutes before the basic coagulant to the coagulation process. The efficiency of surfactant coagulation also increased after the application of powdered clinoptilolite, but to a smaller degree. Then the removal of AS was found to be improved by dosing powdered clinoptilolite simultaneously or with short delay after the addition of the basic coagulant